External focus of attention enhances arm velocities during volleyball spike in young female players - Slovák, Lukáš; Sarvestan, Javad; Iwatsuki, Takehiro; Zahradník, David; Land, William M.; Abdollahipour, Reza (Frontiers in Psychology, 2023)
The aim of this study was to investigate the effect of different volleyball-specific attentional focus instructions on arm velocities of a volleyball spike in young female volleyball players using the Statistical Parametric Mapping method. Twelve young female volleyball players (13.6±0.6 years old, 1.8±0.8 years of experience in volleyball training) were asked to perform a volleyball spike in a standing position in three different attentional focus conditions including internal focus (IF, i.e., pull back your elbow prior to transfer momentum), external focus, (EF, i.e., imagine cracking a whip to transfer momentum), and control (CON, i.e., no-focus instruction). A Qualisys 3D motion capture-system was used to track reflective markers attached to the arm, forearm, and hand. Consequently, four phases of the volleyball spike including wind-up, cocking, acceleration, and follow-through were analyzed. A one-way repeated measure ANOVA using one-dimensional statistical parametric mapping (SPM1d) showed that players achieved greater velocities in the hand (p<.01), forearm (p < .01), and arm (p<.01) using the EF instructions from the start of the wind-up phase to the acceleration phase. Post-hoc (SPM1d-ttests-paired) analyses indicated significantly greater arm, forearm, and hand velocities during the EF condition, compared to CON (p < .01, p < .01, and p < .01 respectively) and IF (p < .01, p < .01, and p < .01 respectively) conditions. These findings suggest that EF instructions had an immediate impact on increasing volleyball spike velocity from the start of the wind-up phase to the acceleration phase prior to ball contact.